2021
DOI: 10.1186/s13048-021-00910-0
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MNX1-AS1 promotes ovarian cancer process via targeting the miR-744-5p/SOX12 axis

Abstract: Purpose Ovarian cancer (OC) is the most common malignancy in women with high mortality. Increasing studies have revealed that long non-coding RNA (lncRNA) MNX1-AS1 has a promoting effect on various cancers. However, the mechanisms of MNX1-AS1 in OC are still unclear. Therefore, this study focused on exploring the mechanisms of MNX1-AS1 in OC. Materials and methods The expression of SOX12 at the protein level was detected by western blot. Cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The significant differential expression between normal and tumour tissues suggested that these genes can serve as hallmark diagnostic markers for various cancers. These observations are in line with previous reports describing overexpression of MNX1 in cancers of the colon [ 15 ], breast [ 11 , 12 ], prostate [ 13 ], and glioma [ 17 ], as well as MNX1 - AS1 in breast [ 28 ], colon [ 29 ], oesophageal [ 30 ], stomach [ 31 ], glioblastoma [ 32 ], liver [ 33 ], lung [ 34 ], ovarian [ 35 , 36 ], and prostate [ 37 ] tumours. MNX1 was not found to be significantly overexpressed in liver cancer samples from TCGA compared to healthy liver tissue from GTEx, despite reports of upregulation in hepatocellular carcinoma [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…The significant differential expression between normal and tumour tissues suggested that these genes can serve as hallmark diagnostic markers for various cancers. These observations are in line with previous reports describing overexpression of MNX1 in cancers of the colon [ 15 ], breast [ 11 , 12 ], prostate [ 13 ], and glioma [ 17 ], as well as MNX1 - AS1 in breast [ 28 ], colon [ 29 ], oesophageal [ 30 ], stomach [ 31 ], glioblastoma [ 32 ], liver [ 33 ], lung [ 34 ], ovarian [ 35 , 36 ], and prostate [ 37 ] tumours. MNX1 was not found to be significantly overexpressed in liver cancer samples from TCGA compared to healthy liver tissue from GTEx, despite reports of upregulation in hepatocellular carcinoma [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…LncRNAs are expected to become molecular markers and therapeutic targets for tumor diagnosis and prognosis (18). The function of several lncRNAs has been revealed in ovarian cancer, such as MALAT1 (19), HOTAIR (20), CCAT1 (21)、NEAT1 ( 22), MNX1-AS1 (23).…”
Section: Discussionmentioning
confidence: 99%
“…34 The overexpression of miR-744-5p inhibits cell proliferation, migration, and invasion. 35 In addition, the downregulation of miR-744-5p was also reported to be associated with signaling pathways related to glucose and lipid metabolism. 36 MiR-330 was also found to promote cell proliferation in human glioblastoma cells and vascular endothelial cells by regulating the SH3-domain GRB2-like 2 and WNT signaling pathways, respectively.…”
Section: Discussionmentioning
confidence: 99%